Composite solid electrolyte layer, method of preparation, secondary battery, and mobile platform
Patent Information
- Application Number
- CN202610245427.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-28
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]本申请所要解决的技术问题是提供一种复合固态电解质层、制备方法、二次电池和移动平台,以解决相关技术中硫化物固态电解质与正、负极片接触的界面处易生成高阻抗的钝化层的问题
本申请实施例所提供的复合固态电解质层包括固态电解质层、第一保护层和第二保护层,沿复合固态电解质层的厚度方向,第一保护层设置于固态电解质层的一侧,第二保护层设置于固态电解质层背离第一保护层的另一侧;固态电解质层包括硫化物固态电解质,第一保护层和第二保护层分别包括氧化物固态电解质。在本申请中,固态电解质层包括硫化物固态电解质,硫化物固态电解质能够提供较高的室温离子电导率,确保电池的离子传输效率;而第一保护层和第二保护层分别包覆于固态电解质层的两侧,由于第一保护层和第二保护层的氧化物固态电解质对空气/水分的稳定性好,能够作为固态电解质层的物理与化学屏障,阻隔空气中的水分和氧气接触固态电解质层的硫化物固态电解质,有利于提升硫化物固态电解质的环境稳定性,避免硫化物固态电解质与正、负极片接触的界面处生成高阻抗的钝化层;同时,第一保护层和第二保护层与正极活性材料直接接触时性能更为稳定,能抑制界面副反应,拓宽电池电压窗口。因此,该复合结构的复合固态电解质层解决了硫化物固态电解质对环境敏感性高以及对正极活性材料兼容性差的问题。
Smart Images

Figure CN122992157A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to a composite solid electrolyte layer, a preparation method, a secondary battery, and a mobile platform. Background Technology
[0002] Solid-state batteries consist of a positive electrode, a solid electrolyte layer, and a negative electrode, which are stacked sequentially. The solid electrolyte layer serves to isolate the positive and negative electrodes and conduct active ions. Among solid electrolyte layers, sulfide solid electrolytes are widely used due to their excellent room-temperature ionic conductivity and good mechanical ductility.
[0003] However, sulfide solid electrolytes are sensitive to moisture and oxygen in the air, and are prone to hydrolysis and oxidation reactions, resulting in poor chemical stability and interfacial properties.
[0004] When solid-state batteries use sulfide solid electrolytes, a high-resistivity passivation layer is easily formed at the interface where the sulfide solid electrolyte contacts the positive and negative electrodes, which leads to accelerated capacity decay and shortened cycle life of the solid-state battery. Summary of the Invention
[0005] The technical problem to be solved by this application is to provide a composite solid electrolyte layer, a preparation method, a secondary battery, and a mobile platform to solve the problem in related technologies that a high-resistivity passivation layer is easily formed at the interface where the sulfide solid electrolyte contacts the positive and negative electrodes.
[0006] To solve the above problems, this application provides the following technical solution: This application proposes a composite solid electrolyte layer, including a solid electrolyte layer, a first protective layer and a second protective layer. Along the thickness direction of the composite solid electrolyte layer, the first protective layer is disposed on one side of the solid electrolyte layer, and the second protective layer is disposed on the other side of the solid electrolyte layer opposite to the first protective layer. The solid electrolyte layer includes a sulfide solid electrolyte, and the first protective layer and the second protective layer each include an oxide solid electrolyte.
[0007] In some embodiments, the thickness of the solid electrolyte layer is 1~2 mm; And / or, in the thickness direction of the composite solid electrolyte layer, the dimensions of the first protective layer and the second protective layer are 25~100nm respectively.
[0008] And / or, the solid electrolyte layer further includes lithium halide.
[0009] In some embodiments, the lithium halide in the solid electrolyte layer accounts for 1% to 5% by mass; And / or, the lithium halide includes at least one of LiF, LiCl, LiBr and LiI.
[0010] This application also provides a method for preparing a composite solid electrolyte layer, including: Sulfide solid electrolytes are made into solid electrolyte layers; A first protective layer and a second protective layer are respectively disposed on both sides of the solid electrolyte layer to obtain a composite solid electrolyte layer, wherein both the first protective layer and the second protective layer comprise an oxide solid electrolyte.
[0011] In some embodiments, a first protective layer and a second protective layer are respectively provided on both sides of the solid electrolyte layer, including: Using the oxide solid electrolyte as a target, magnetron sputtering is performed on both sides of the solid electrolyte layer to form the first protective layer and the second protective layer on the two sides of the solid electrolyte layer, respectively.
[0012] In some embodiments, the magnetron sputtering parameters include: a sputtering source of radio frequency sputtering source, a sputtering power of 100~200W, a sputtering pressure of 0.5~1.5Pa, a sputtering distance of 2~20cm, a sputtering atmosphere of argon and / or nitrogen, and a sputtering time of 10~20min.
[0013] In some embodiments, the process of forming a solid electrolyte layer from a sulfide solid electrolyte includes: Pressure is applied to the sulfide solid electrolyte to form the solid electrolyte layer, wherein the applied pressure is 150~200MPa.
[0014] In some embodiments, the process of forming a solid electrolyte layer from a sulfide solid electrolyte includes: The sulfide solid electrolyte is mixed with lithium halide to form the solid electrolyte layer.
[0015] This application also proposes a secondary battery, including the above-described composite solid electrolyte layer or the composite solid electrolyte layer prepared by the above-described method. The secondary battery further includes a positive electrode and a negative electrode, and the composite solid electrolyte layer is disposed between the positive electrode and the negative electrode.
[0016] This application also proposes a mobile platform, including the aforementioned secondary battery, which serves as the power supply for the mobile platform.
[0017] Compared with related technologies, the embodiments of this application have the following advantages: The composite solid electrolyte layer provided in this application embodiment includes a solid electrolyte layer, a first protective layer, and a second protective layer. Along the thickness direction of the composite solid electrolyte layer, the first protective layer is disposed on one side of the solid electrolyte layer, and the second protective layer is disposed on the other side of the solid electrolyte layer opposite to the first protective layer. The solid electrolyte layer includes a sulfide solid electrolyte, and the first and second protective layers each include an oxide solid electrolyte. In this application, the solid electrolyte layer includes a sulfide solid electrolyte, which can provide high room temperature ionic conductivity, ensuring the ion transport efficiency of the battery. The first and second protective layers respectively cover both sides of the solid electrolyte layer. Because the oxide solid electrolytes of the first and second protective layers have good stability against air / moisture, they can act as physical and chemical barriers for the solid electrolyte layer, preventing moisture and oxygen in the air from contacting the sulfide solid electrolyte of the solid electrolyte layer. This helps improve the environmental stability of the sulfide solid electrolyte and avoids the formation of a high-resistance passivation layer at the interface where the sulfide solid electrolyte contacts the positive and negative electrode plates. Simultaneously, the first and second protective layers are more stable when in direct contact with the positive electrode active material, suppressing interfacial side reactions and widening the battery voltage window. Therefore, the composite solid electrolyte layer of this composite structure solves the problems of high environmental sensitivity and poor compatibility with positive electrode active materials of sulfide solid electrolytes. Attached Figure Description
[0018] Figure 1 This is a schematic diagram of the composite solid electrolyte layer according to an embodiment of this application; Figure label: 1. Solid electrolyte layer; 2. First protective layer; 3. Second protective layer; X, thickness direction of the composite solid electrolyte layer. Detailed Implementation
[0019] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the fixed scope of this application.
[0020] In related technologies, sulfide solid electrolytes are highly sensitive to moisture and oxygen in the air, and are prone to hydrolysis and oxidation reactions, exhibiting poor chemical stability and interfacial performance. Furthermore, when the battery is charged to high voltage, the positive electrode active materials, such as high-nickel ternary or lithium-rich manganese-based materials, are in a highly oxidized state. Due to the thermodynamic instability of sulfur ions in the sulfide solid electrolyte, they are easily oxidized by the highly oxidized positive electrode active materials, generating products with poor insulation or conductivity, such as sulfur, polysulfides, and phosphates. This forms a high-resistance passivation layer at the interface between the positive electrode and the sulfide solid electrolyte, hindering lithium-ion transport efficiency and leading to problems such as a surge in battery internal resistance, capacity decay, and shortened cycle life.
[0021] To address the above problems, embodiments of this application provide a composite solid electrolyte layer. (Refer to...) Figure 1 As shown, the composite solid electrolyte layer includes a solid electrolyte layer 1, a first protective layer 2, and a second protective layer 3. Along the thickness direction X of the composite solid electrolyte layer, the first protective layer 2 is disposed on one side of the solid electrolyte layer 1, and the second protective layer 3 is disposed on the other side of the solid electrolyte layer 1 opposite to the first protective layer 2. In this embodiment, the composite solid electrolyte layer has a solid electrolyte layer 1 as the central layer, with a first protective layer 2 and a second protective layer 3, comprising an oxide solid electrolyte, respectively disposed on both sides of the solid electrolyte layer 1. The solid electrolyte layer 1 includes a sulfide solid electrolyte, which provides high room temperature ionic conductivity, ensuring the battery's ion transport efficiency. The first protective layer 2 and the second protective layer 3 cover both sides of the solid electrolyte layer 1. Because the oxide solid electrolytes in the first and second protective layers 2 and 3 have good stability against air / moisture, they can act as physical and chemical barriers for the solid electrolyte layer 1, preventing moisture and oxygen in the air from contacting the sulfide solid electrolyte. This improves the environmental stability of the sulfide solid electrolyte and prevents the formation of a high-resistance passivation layer at the interface between the sulfide solid electrolyte and the positive and negative electrodes. Simultaneously, the first and second protective layers 2 and 3 exhibit more stable performance when in direct contact with the positive electrode active material, suppressing interfacial side reactions and widening the battery voltage window. Therefore, this composite solid electrolyte layer solves the problems of high environmental sensitivity and poor compatibility with positive electrode active materials associated with sulfide solid electrolytes.
[0022] Sulfide solid electrolytes include Li6PS5Cl and Li 10 GeP2S 12 (LGPS) and Li7P3S 11 At least one of the following, the first protective layer 2 and the second protective layer 3 respectively comprise an oxide solid electrolyte, the oxide solid electrolyte comprising Li7La3Zr2O 12 (LLZO), Li 1.3 Al0.3 Ti 1.7 (PO4)3 (LATP) and Li 6.4 La3Zr 1.4 Ta 0.6 O 12 At least one of (LLZTO).
[0023] In some embodiments, the thickness of the solid electrolyte layer 1 is 1-2 mm. Within this thickness range, the solid electrolyte layer 1 provides sufficient ion conduction pathways to ensure the battery has low internal resistance and high energy efficiency. Simultaneously, this thickness range provides sufficient mechanical strength and flexibility, making it less prone to damage, which is beneficial for ensuring the lithium-ion transport efficiency and structural stability of the solid electrolyte layer 1. In some embodiments, the thickness of the solid electrolyte layer 1 is 1 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.5 mm, 1.7 mm, 1.9 mm, or 2 mm.
[0024] In some embodiments, the dimensions of the first protective layer 2 and the second protective layer 3 in the thickness direction X of the composite solid electrolyte layer are 25~100 nm, respectively. Controlling the thickness range within 25~100 nm helps to form a first protective layer 2 and a second protective layer 3 with high continuity and density, thereby ensuring that the first protective layer 2 and the second protective layer 3 can effectively isolate the solid electrolyte layer 1 from direct contact with air, moisture, and positive electrode active material. At the same time, controlling the thickness range of the first protective layer 2 and the second protective layer 3 to 25~100 nm also reduces the ion transport resistance of the first protective layer 2 and the second protective layer 3 themselves, ensuring that lithium ions can pass through the solid-solid interface between the first protective layer 2 or the second protective layer 3 and the solid electrolyte layer 1 more efficiently from the electrode side, reducing the interface impedance, thereby improving the overall ion transport rate of the composite solid electrolyte layer.
[0025] In some embodiments, the dimensions of the first protective layer 2 and the second protective layer 3 in the thickness direction X of the composite solid electrolyte layer are 25 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, respectively.
[0026] In some embodiments, the solid electrolyte layer 1 further includes lithium halides, which fill the gaps between the sulfide solid electrolyte particles, improving the physical contact between the sulfide solid electrolyte particles and thus improving the ion conduction performance of the solid electrolyte layer 1. This reduces the impedance when lithium ions pass through the solid-solid interface between the first protective layer 2 or the second protective layer 3 and the solid electrolyte layer 1, which is beneficial for improving the ion transport rate of the solid electrolyte layer 1. In the solid electrolyte layer 1, the mass percentage of lithium halides is controlled at 1% to 5%, which can improve the ion transport rate by introducing halide ions while avoiding damage to the main structure of the sulfide solid electrolyte due to excessive addition.
[0027] In some embodiments, lithium halides include at least one of LiF, LiCl, LiBr, and LiI. In the solid electrolyte layer 1, the mass percentage of lithium halides is 1%, 2%, 3%, 4%, or 5%.
[0028] In some embodiments, a method for preparing a composite solid electrolyte layer is also provided, comprising the following steps: Step 1: Prepare a solid electrolyte layer from the sulfide solid electrolyte.
[0029] A solid electrolyte layer is formed by applying pressure to a sulfide solid electrolyte, wherein the applied pressure is controlled between 150 MPa and 200 MPa.
[0030] In some embodiments, a solid electrolyte layer can also be formed by mixing a sulfide solid electrolyte with lithium halide and applying pressure.
[0031] In some embodiments, a solid electrolyte layer is prepared by cold pressing, specifically including: in an inert atmosphere glove box, sulfide solid electrolyte powder (or a uniformly mixed sulfide solid electrolyte powder and lithium halide powder) is loaded into a mold and cold-pressed at room temperature under a pressure of 150~200MPa to form a dense sheet. During the cold pressing process, it is necessary to ensure that the surface of the sheet is flat and free of macroscopic cracks so that the sheet has uniform thickness and structural integrity. Subsequently, the surface of the sheet needs to be cleaned (e.g., by purging with inert gas) and dried at a temperature of 80~100°C for 4~6 hours to remove any trace amounts of moisture that may be adsorbed in the sheet, finally obtaining a solid electrolyte layer with a thickness of 1~2mm.
[0032] In some embodiments, sulfide solid electrolyte powder (or a thoroughly mixed sulfide solid electrolyte powder and halide powder) can be loaded into a circular mold to press and form a circular solid electrolyte layer with a diameter of 10-15 mm and a thickness of 1-2 mm.
[0033] Step 2: A first protective layer and a second protective layer are respectively set on both sides of the solid electrolyte layer to obtain a composite solid electrolyte layer; wherein both the first protective layer and the second protective layer include oxide solid electrolyte.
[0034] A first protective layer and a second protective layer are deposited on both sides of the solid electrolyte layer using magnetron sputtering. Magnetron sputtering is a physical vapor deposition process that uses a magnetic field to confine and enhance glow discharge plasma to sputter atoms or molecules of a target material into a substrate surface in a vacuum environment, thereby forming a thin film on the substrate surface.
[0035] In the preparation of the composite solid electrolyte layer, an oxide solid electrolyte is used as the target material, and the solid electrolyte layer is subjected to magnetron sputtering to form a first protective layer and a second protective layer on both sides of the solid electrolyte layer, respectively, to obtain the composite solid electrolyte layer.
[0036] The magnetron sputtering parameters include: the sputtering source is an RF sputtering source, the sputtering power is 100~200W, and the sputtering pressure is 0.5~1.5Pa, to ensure that the oxide solid electrolyte particles have sufficient kinetic energy while avoiding excessive kinetic energy that could damage the solid electrolyte layer; at a sputtering distance of 2-20cm and a sputtering time of 10-20min, a dense and uniform first and second protective layer is formed; and the sputtering atmosphere is argon and / or nitrogen to avoid oxidation of the sulfide solid electrolyte by active atmospheres such as oxygen.
[0037] In some embodiments, when performing magnetron sputtering, the parameters are set as follows: sputtering source is an RF sputtering source, sputtering power is 100W, sputtering pressure is 0.5Pa, sputtering distance is 2cm, sputtering atmosphere is argon, and sputtering time is 10min; or, the parameters can be set as follows: sputtering source is an RF sputtering source, sputtering power is 200W, sputtering pressure is 1Pa, sputtering distance is 15cm, sputtering atmosphere is a mixture of argon and nitrogen, and sputtering time is 15min.
[0038] In the specific preparation process, an oxide solid electrolyte is used as the target material in a magnetron sputtering device, and high-purity argon is used as the sputtering gas. A solid electrolyte layer with a thickness of 1~2mm is placed on the coating target stage of the sputtering device, the sputtering parameters are adjusted, and the oxide solid electrolyte is sputtered by magnetron sputtering. Finally, a first protective layer and a second protective layer with a thickness of 25~100nm are formed on both sides of the solid electrolyte layer, thus obtaining a composite solid electrolyte layer.
[0039] In some embodiments, a secondary battery is also provided, including the composite solid electrolyte layer described above or the composite solid electrolyte layer prepared by the above-described method. The secondary battery further includes a positive electrode and a negative electrode, with the composite solid electrolyte layer disposed between the positive and negative electrode. It should be noted that the composite solid electrolyte layer in the secondary battery disclosed in this application has the same structure as the composite solid electrolyte layer in the above embodiments, and its beneficial effects are similar. Therefore, it will not be repeated here; relevant details can be found in the descriptions of the composite solid electrolyte layer embodiments.
[0040] In some embodiments, the positive electrode sheet includes a positive current collector and a positive active material layer disposed on the positive current collector. The positive active material layer includes a positive active material, a binder, and a conductive agent. In some embodiments, the positive current collector may be an aluminum foil or an aluminum alloy foil. The positive active material includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, nickel-cobalt-manganese ternary materials, and nickel-cobalt-aluminum ternary materials.
[0041] In some embodiments, the positive electrode sheet is prepared as follows: the positive active material, binder and conductive agent are dispersed in a solvent such as N-methylpyrrolidone to form a positive electrode slurry; the positive electrode slurry is coated on the positive current collector; after drying, a negative active material layer is formed on the negative current collector; and after further cold pressing, cutting and slitting processes, the positive electrode sheet can be obtained.
[0042] The negative electrode includes a negative current collector and a negative active material layer disposed on at least one side of the negative current collector. The negative active material layer includes a negative active material, a conductive agent, and a binder. The negative current collector serves as the carrier of the negative active material layer and the channel for electron conduction. Its material is preferably copper foil or copper alloy foil due to its good conductivity, adhesion to the negative active material layer, and electrochemical stability at the battery operating potential. The negative active material includes at least one of artificial graphite, natural graphite, mesophase carbon microspheres, soft carbon, hard carbon, silicon-based materials, and lithium titanate.
[0043] In some embodiments, the negative electrode active material, binder, conductive agent and solvent are mixed evenly to obtain a negative electrode slurry. Subsequently, the negative electrode slurry is coated onto a negative electrode current collector, and after drying, a negative electrode active material layer is formed on the negative electrode current collector. After further cold pressing, cutting, slitting and other processes, a negative electrode sheet is obtained.
[0044] In some embodiments, the binder in the positive and negative electrode sheets provides sufficient adhesion and structural integrity to enhance the bond between the active material layer and the current collector, preventing detachment during cycling. It also provides the necessary flexibility to buffer volume changes during charging and discharging. The binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene-propylene terpolymer, ethylene-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.
[0045] The conductive agents in the positive and negative electrode sheets can form a conductive network within the electrodes, reducing internal resistance and improving the rate performance of the battery. Conductive agents can include acetylene black, carbon fiber, carbon nanotubes, Ketjen black, artificial graphite, natural graphite, hard carbon, soft carbon, carbon black, graphene, etc.
[0046] In some embodiments, the solvents in the positive and negative electrode slurries include at least one of ethanol, N-methylpyrrolidone (NMP), acetone, acetonitrile, toluene, xylene, anisole, heptane, decane, ethyl acetate, ethyl propionate, and butyl butyrate.
[0047] In some embodiments, the positive electrode active material layer further includes a solid electrolyte, which, by distributing the solid electrolyte in the positive electrode active material layer, constructs a relatively efficient ion transport channel within the positive electrode active material layer. In some embodiments, the negative electrode active material layer further includes a solid electrolyte, which, by distributing the solid electrolyte in the negative electrode active material layer, constructs a relatively efficient ion transport channel within the negative electrode active material layer. The solid electrolyte layer disposed between the positive and negative electrode plates serves as an ion transport bridge throughout the solid-state battery, working synergistically with the ion transport channels within the positive and negative electrode plates to ensure that lithium ions can rapidly and stably complete migration and cycling throughout the entire battery during charging and discharging. The solid electrolyte includes at least one of oxide solid electrolyte, sulfide solid electrolyte, and halide solid electrolyte.
[0048] In some embodiments, during the preparation of a secondary battery, in a glove box filled with argon (H2O < 1 ppm, O2 < 1 ppm), a composite solid electrolyte layer is stacked on the negative electrode, and a positive electrode is stacked on the side of the composite solid electrolyte layer away from the negative electrode to obtain a bare cell; the bare cell is then placed in an outer packaging shell (aluminum-plastic film) and subjected to vacuum sealing, isostatic pressing (pressure of 100 MPa), formation and other processes to obtain a secondary battery.
[0049] In some embodiments, a mobile platform is also provided, which includes a secondary battery as a power supply for the mobile platform. It should be noted that the secondary battery disclosed in this application has the same structure as the secondary battery in the above embodiments, and its beneficial effects are similar. Therefore, it will not be repeated here; relevant details can be found in the description of the secondary battery embodiments.
[0050] In some embodiments, the mobile platform is a vehicle, including but not limited to electric vehicles, hybrid vehicles, range-extended vehicles, electric commercial vehicles, electric construction machinery, electric ships, and electric rail transit vehicles.
[0051] In some embodiments, the mobile platform is a robot, including but not limited to industrial robots, service robots, special-purpose robots, mobile robots, bionic robots, drones, etc.
[0052] In some embodiments, the mobile platform is a mobile energy storage device, including but not limited to mobile energy storage vehicles, mobile energy storage power stations, and portable energy storage devices.
[0053] In all the above embodiments, the secondary batteries serve as the power supply for the mobile platform, providing electrical energy for the platform's drive, control, operation, and auxiliary systems.
[0054] To make the inventive objectives, technical solutions, and beneficial effects of this application clearer, the present application is further described below with reference to embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application. Unless otherwise specified, the reagents and instruments used in the embodiments and comparative examples are all commercially available, and the experimental operations are performed in accordance with the product instructions and standard experimental procedures.
[0055] Example 1 (1) Preparation of solid electrolyte layer The sulfide solid electrolyte Li6PS5Cl powder was filled into a mold and pressed in a cold press to obtain a circular sheet with a diameter of 10 mm and a thickness of 1 mm. The circular sheet was then cleaned and placed in a drying oven to dry at 60°C for 6 hours to obtain a solid electrolyte layer.
[0056] (2) Preparation of composite solid electrolyte layer In magnetron sputtering equipment, Li7La3Zr2O is selected. 12 Using LLZO as the target material, and introducing high-purity argon gas with a concentration of 99.99%, the sputtering pressure was set to 1 Pa, the sputtering power to 200 W, the sputtering time to 10 min, and the sputtering distance to 60 mm. A first protective layer and a second protective layer of the same thickness were formed on both sides of the solid electrolyte layer, with the thicknesses of the first protective layer and the second protective layer being 60 nm, respectively.
[0057] (3) Preparation of positive electrode sheet LiNi with a mass ratio of 94:3:2:1 0.6 Mn 0.2 Co 0.2 O2, conductive carbon black, styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed and an appropriate amount of N-methylpyrrolidone solvent is added to prepare a positive electrode slurry; then, the positive electrode slurry is coated on an aluminum foil current collector; and then dried at 80°C for 30 minutes to completely remove the solvent, resulting in a positive electrode sheet with a thickness of 150 μm.
[0058] (4) Preparation of negative electrode sheet A negative electrode slurry was prepared by mixing pure silicon, conductive carbon black, styrene-butadiene rubber and sodium carboxymethyl cellulose in a mass ratio of 93:3:2:2, and adding an appropriate amount of N-methylpyrrolidone solvent. The negative electrode slurry was then coated onto the surface of a copper foil current collector. The mixture was then dried at 80°C for 30 minutes to completely remove the solvent, resulting in a negative electrode sheet with a thickness of 50 μm.
[0059] (5) Assemble solid-state batteries In an argon-filled glove box (H2O < 1 ppm, O2 < 1 ppm), a composite solid electrolyte layer is stacked on the negative electrode, and a positive electrode is stacked on the side of the composite solid electrolyte layer opposite to the negative electrode, resulting in a bare cell. The bare cell is then placed in an outer packaging shell (aluminum-plastic film) and subjected to vacuum sealing, isostatic pressing (pressure 100 MPa), and formation processes to obtain a solid-state battery.
[0060] Examples 2-8 The difference between Examples 2-8 and Example 1 is that the thickness of the solid electrolyte layer and the sulfide solid electrolyte in step (1) were adjusted; and the thickness of the first protective layer and the second protective layer and the oxide solid electrolyte in step (2) were adjusted respectively.
[0061] Examples 9-10 The difference between Examples 9 and 10 and Example 1 is that in step (1), the sulfide solid electrolyte Li6PS5Cl powder and lithium iodide powder are mixed evenly and then filled into a mold. In Example 9, the mass percentage of lithium iodide in the mixture of sulfide solid electrolyte Li6PS5Cl powder and lithium iodide powder is 1%. In Example 10, the mass percentage of lithium iodide in the mixture of sulfide solid electrolyte Li6PS5Cl powder and lithium iodide powder is 5%.
[0062] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that step (2) is not performed, and when performing step (5), the solid electrolyte layer prepared in step (1) is stacked on the negative electrode in a glove box filled with argon (H2O < 1 ppm, O2 < 1 ppm), and the positive electrode is stacked on the side of the solid electrolyte layer away from the negative electrode to obtain a bare cell. The bare cell is placed in an outer packaging shell (aluminum-plastic film) and vacuum-sealed, isostatically pressed (pressure of 100 MPa), and formed to obtain a solid-state battery.
[0063] The relevant parameters for solid-state batteries prepared through the examples and comparative examples are shown in Table 1. It should be noted that since the structures of the first protective layer and the second protective layer are completely identical, only the relevant parameters of the first protective layer are shown in Table 1.
[0064] Table 1
[0065] The composite solid electrolyte layer and solid battery of the above embodiments, and the solid electrolyte layer and solid battery of Comparative Example 1 were subjected to performance tests. The test methods included: (1) Chemical stability test: After exposing the composite solid electrolyte layer of each embodiment and the solid electrolyte layer of the comparative example to an environment with an air humidity of 5% for 1 hour, the content of H2S gas was detected and the appearance was observed to see if oxidation or peeling occurred.
[0066] (2) Interface resistance test: After exposing the composite solid electrolyte layer of each embodiment and the solid electrolyte layer of the comparative example to an environment with an air humidity of 5% for 1 hour, they were sealed and transferred to an argon atmosphere glove box. Two lithium foils were tightly attached to both sides of the composite solid electrolyte layer of each embodiment and to both sides of the solid electrolyte layer of the comparative example to form lithium symmetric batteries. The lithium symmetric batteries were left to stand for 3 hours to allow the interface to fully contact. The test was performed using an electrochemical workstation: a sinusoidal AC voltage perturbation with an amplitude of 10 mV was applied in the frequency range of 1 MHz to 0.1 Hz, and the interface resistance value was measured.
[0067] (3) First discharge specific capacity test: For the solid-state batteries prepared in each embodiment and comparative example, they were charged to 4.3 V at a constant current of 0.1 C, then charged to 4.3 V at a constant voltage, and then discharged to 3.0 V at 0.1 C to test the first discharge specific capacity of the solid-state battery.
[0068] (4) Cyclic performance test: For the solid-state batteries prepared in each embodiment and comparative example, the initial discharge capacity C1 was measured after one charge-discharge cycle at a temperature of 25 ℃, 3 V~4.3 V and 1C current density. The discharge capacity C2 was obtained after 100 cycles at 1C current density. The capacity retention rate after 100 cycles was calculated as C2 / C1.
[0069] Table 2
[0070] As can be seen from Table 2, the composite solid electrolyte layer and solid battery performance of each embodiment of this application are superior to those of Comparative Example 1. This indicates that the first and second protective layers provided on both sides of the sulfide solid electrolyte layer can act as physical and chemical barriers to the solid electrolyte layer, preventing moisture and oxygen in the air from contacting the sulfide solid electrolyte layer, thereby suppressing side reactions, improving interfacial compatibility, and enhancing the air stability, interfacial stability, and cycle life of the solid battery.
[0071] Although preferred embodiments of the present application have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of the embodiments of the present application.
[0072] The above provides a detailed description of the composite solid electrolyte layer, its preparation method, secondary battery, and mobile platform provided in this application. Specific examples have been used to illustrate the principles and implementation methods of this application. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.
Claims
1. A composite solid electrolyte layer, characterized in that, It includes a solid electrolyte layer, a first protective layer and a second protective layer. Along the thickness direction of the composite solid electrolyte layer, the first protective layer is disposed on one side of the solid electrolyte layer, and the second protective layer is disposed on the other side of the solid electrolyte layer opposite to the first protective layer. The solid electrolyte layer includes a sulfide solid electrolyte, and the first protective layer and the second protective layer each include an oxide solid electrolyte.
2. The composite solid electrolyte layer according to claim 1, characterized in that, The thickness of the solid electrolyte layer is 1~2mm; And / or, in the thickness direction of the composite solid electrolyte layer, the dimensions of the first protective layer and the second protective layer are 25~100 nm, respectively. And / or, the solid electrolyte layer further includes lithium halide.
3. The composite solid electrolyte layer according to claim 2, characterized in that, In the solid electrolyte layer, the lithium halide accounts for 1% to 5% by mass; And / or, the lithium halide includes at least one of LiF, LiCl, LiBr and LiI.
4. The method for preparing the composite solid electrolyte layer according to any one of claims 1 to 3, characterized in that, include: Sulfide solid electrolytes are made into solid electrolyte layers; A first protective layer and a second protective layer are respectively disposed on both sides of the solid electrolyte layer to obtain a composite solid electrolyte layer, wherein both the first protective layer and the second protective layer comprise an oxide solid electrolyte.
5. The method for preparing the composite solid electrolyte layer according to claim 4, characterized in that, A first protective layer and a second protective layer are respectively disposed on both sides of the solid electrolyte layer, including: Using the oxide solid electrolyte as a target, magnetron sputtering is performed on both sides of the solid electrolyte layer to form the first protective layer and the second protective layer on the two sides of the solid electrolyte layer, respectively.
6. The method for preparing the composite solid electrolyte layer according to claim 5, characterized in that, The magnetron sputtering parameters include: the sputtering source is an RF sputtering source, the sputtering power is 100~200W, the sputtering pressure is 0.5~1.5Pa, the sputtering distance is 2~20cm, the sputtering atmosphere is argon and / or nitrogen, and the sputtering time is 10~20min.
7. The method for preparing the composite solid electrolyte layer according to any one of claims 4 to 6, characterized in that, The process of forming a solid electrolyte layer from a sulfide solid electrolyte includes: Pressure is applied to the sulfide solid electrolyte to form the solid electrolyte layer, wherein the applied pressure is 150~200MPa.
8. The method for preparing the composite solid electrolyte layer according to any one of claims 4 to 7, characterized in that, The process of forming a solid electrolyte layer from a sulfide solid electrolyte includes: The sulfide solid electrolyte is mixed with lithium halide to form the solid electrolyte layer.
9. A secondary battery, characterized in that, The secondary battery includes a composite solid electrolyte layer prepared by the method of preparing the composite solid electrolyte layer according to any one of claims 1 to 3 or any one of claims 4 to 8, and the secondary battery further includes a positive electrode and a negative electrode, wherein the composite solid electrolyte layer is disposed between the positive electrode and the negative electrode.
10. A mobile platform, characterized in that, It includes the secondary battery as described in claim 9, wherein the secondary battery serves as the power supply for the mobile platform.